BS EN 60601-2-35 AMD1. Medical electrical equipment. Part 2-35. Particular requirements for the basic safety and essential performance of heating devices using blankets, pads and mattresses and intended for heating in medical use (25th June 2021) - British Standards Institution,
No abstract available